Pala “Kearifan yang Menyelamatkan” Kajian Kritis Pengakuan Biological Asset: PSAK 69 - M. Dhanutirto F Tuwow (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2019)
The aim of this research is to criticize the accounting treatment of biological assets regulated in PSAK 69. The research uses a critical paradigm, by lowering social theory and then formulated with a qualitative approach to ethnometodology studies, to see the meaning of daily activities which are agreed by the indigenous people of Moloku Kie Raha ( North Maluku). The majority of the population here are Nutmeg farmers, nutmeg is an economic and social symbol here. Interestingly, when the harvest arrives and the nutmeg that has fallen to the ground is entitled to be taken by anyone, except the owner of these assets. Here the author wants to criticize the recognition of biological asset objects in PSAK 69, where this kind of local wisdom is not heeded and stated in the rules that recognize it from the accounting side itself.